New and remarkable Asian and North African species of Colletes Latreille (Hymenoptera: Colletidae) - Kuhlmann, Michael; Proshchalykin, Maxim Yu. (Zootaxa, 2015)
In addition to previous studies on Asian and North African species of Colletes Latreille, we here further report records of 25 rarely collected and little known species. Six new species are described: Colletes comaticus Kuhlmann, sp. nov. (♂, Iran), C. uzbekus Kuhlmann & Proshchalykin, sp. nov. (♀, Uzbekistan), C. kazakhus Kuhlmann & Proshchalykin, sp. nov. (♂, Kazakhstan), C. tibestensis Kuhlmann, sp. nov. (♀, Chad, Sudan), C. packeri Kuhlmann, sp. nov. (♀, ♂, Thailand, Laos) and C. jemeniticus Kuhlmann, sp. nov. (♂, Yemen). The female of C. issykkuli Kuhlmann 2003 and the male of C. kaline Kuhlmann & Proshchalykin 2013 are here described for the first time. New synonymies are established for Colletes uralensis Noskiewicz 1936 (=C. kipyatkovi Kuhlmann & Proshchalykin 2013, syn. nov.) and C. salsolae Cockerell 1934 (=C. omanus Kuhlmann 2003, syn. nov.).